2018
DOI: 10.3389/fimmu.2018.00713
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Ligands Can Trigger T Cell Receptor Signaling Without CD45 Segregation

Abstract: How T cell receptors (TCRs) are triggered to start signaling is still not fully understood. It has been proposed that segregation of the large membrane tyrosine phosphatase CD45 from engaged TCRs initiates signaling by favoring phosphorylation of immunoreceptor tyrosine-based activation motifs (ITAMs) in the cytoplasmic domains of CD3 molecules. However, whether CD45 segregation is important to initiate triggering is still uncertain. We examined CD45 segregation from TCRs engaged to anti-CD3 scFv with high or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 87 publications
(113 reference statements)
1
17
0
Order By: Relevance
“…Because CD45 is excluded it has been proposed that the segregation of CD45 itself may be sufficient to initiate TCR signaling (26). However, studies using tethered antibodies that bind to the TCR with high affinity indicate that exclusion of CD45 is not a strict requirement (64). Additional studies have reported that the T cell:APC synapse also functions as a site of sustained signaling and receptor downregulation upon strong stimulation (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…Because CD45 is excluded it has been proposed that the segregation of CD45 itself may be sufficient to initiate TCR signaling (26). However, studies using tethered antibodies that bind to the TCR with high affinity indicate that exclusion of CD45 is not a strict requirement (64). Additional studies have reported that the T cell:APC synapse also functions as a site of sustained signaling and receptor downregulation upon strong stimulation (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its abundance and its large extracellular domain, CD45 has been used by many authors over years as a tool molecule, which can be used to efficiently immobilize T cells without affecting their biology 61 , although some reports indicate that CD45 segregation may nevertheless impact T cell activation 62 , depending on the isotype of the antibody used 63 . Recent reports show that CD45 segregation is not required to stimulate Jurkat T cells by immobilized recombinant monovalent antibodies raised against CD3 64 . We tested other antibodies, such as aCD43 or aMHCI following ref.…”
Section: Resultsmentioning
confidence: 99%
“…Another important observation at a larger-length scale was that the exclusion of phosphatase CD45 from the TCR was also different between the ligations of the TCR with an agonist or antagonist. The exclusion of CD45 occurred only when the TCR binds to an agonist [ 13 , 78 , 81 , 82 ]. The exclusion of CD45 determines the signaling outcome by modulating the degree of ITAM phosphorylation, and thus, this can be a critical mechanism to discriminate agonist against antagonist.…”
Section: Mechanical Regulation Of T Cell Activationmentioning
confidence: 99%